Fine Arts Building, Alaska-Yukon-Pacific-Exposition, Seattle, Washington, 1909 - University of Washington Libraries. Special Collections Division (1909)
Caption on image: Fine Arts Palace. Printed on verso: 55. The Fine Arts Palace contains in its various halls, 531 paintings and pieces of sculpture. Many of the canvasses are by old famous painters. The building is permanent and reverts to Washington University. 1909. The Alaska-Yukon-Pacific Exposition. Official Photograph. Published by Robert A. Reid. 488 Arcade. Made in Seattle. PH Coll 777 Reid.55 (See also PH Coll 78.162) To order a reproduction, inquire about permissions, or for information about prices see: http://www.lib.washington.edu/specialcollections/services/reproduction/reproduction Please cite the Order Number